Peran Standar Satuan Harga (SSH) dalam Meningkatkan Akuntabilitas dan Efisiensi Anggaran Pengembangan SDM Daerah: Studi pada Pemerintah Kabupaten Berau - Robianto (Badan Pengembangan Sumber Daya Manusia Provinsi Kalimantan Timur, 2025)
This study investigates the function of the Standard Unit Price (SSH) in improving accountability and budgetary efficiency for human resource development within the Berau Regency Government. SSH, as a tool for regional budget control, is essential for attaining transparent and effective financial governance; nevertheless, its application in the realm of regional human resource development has been suboptimal. The study used a qualitative methodology with an explanatory case study design, incorporating 27 key informants from the Regional Financial and Asset Management Agency, the Regional Civil Service Agency, and associated OPDs. We collected data through comprehensive interviews, participatory observation, and a study of budget documents. The research findings indicate that the use of SSH markedly enhances budget accountability via cost standardization, planning transparency, and audit facilitation. SSH achieved budgetary reductions of 17.3% for competency development programs and 22.1% for education and training operations in terms of efficiency. Challenges emerged around the necessity to adapt SSH to market pricing fluctuations, restricted flexibility for particular requirements, and the capability of deploying human resources. This study advocates for the formulation of adaptive SSH policies, the fortification of information systems integration, and the augmentation of financial management officials’ capabilities to optimize the function of SSH in bolstering accountability and budgetary efficiency for regional human resource development.